The lexicographical treatment of idioms in business dictionaries from the point of view of the translator as user - Vicente, Esther Fraile (HERMES - Journal of Language and Communication in Business, 2008)
Economic language presents a hybrid nature. Unlike other LSPs, this discourse shows a high degree of emotive meaning, abstract processes like metaphor, which bring about the great number of idioms used in business English, and the complexity involved in their translation into Spanish. The analysis of the lexicographical treatment of ﬁve business idioms in nineteen dictionaries of economics (monolingual, bilingual, and multilingual) reveals that specialized lexicographical resources should improve their treatment of idioms and other phraseological units if they are to respond to the needs of users like translators. It is suggested that specialized works should include idioms as lemmas, offer more types of syntactic-semantic information and structure it more systematically, for example, by basing their entries on the conceptual structure of economy.